PENGARUH SALES GROWTH, CAPITAL INTENSITY DAN KEBIJAKAN UTANG TERHADAP AGRESIVITAS PAJAK - Ariani, Adila; Syamsul Asmedi (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to analyze the effect of Sales Growth, Capital Intensity, and Debt Policy on tax aggressiveness (an empirical study on Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange for the period 2019-2023). This quantitative research utilizes secondary data obtained from the official website of the Indonesia Stock Exchange (IDX) in the form of annual financial reports. The sampling method used in this study is purposive sampling, resulting in a sample of 35 companies from a total of 129 Consumer Non-Cyclicals sector companies over five years, yielding 175 data samples. The analysis employed is Panel Data Regression Analysis using EViews 12. The results indicate that, simultaneously, sales growth, capital intensity, and debt policy have an effect on tax aggressiveness. Partially, each of the three independent variables tested—Sales Growth, Capital Intensity, and Debt Policy—has an effect on Tax Aggressiveness. Keywords: Sales Growth, Capital Intensity, Debt Policy, Tax Aggressiveness.